Environment case study: Forestry and water management in Thailand: A win win wituation - MAMOON, Dawood (Turkish Economic Review, 2018)
Abstract. The article offers a critique for the argument that forest clearing by the people in the upper areas of the watershed is the main reason for decrease in water supply. Instead he considers increased demand of water for agricultural activity especially during dry season by both upstream and downstream areas as the main cause of water shortage. Thus unlike previous studies, who blame people from upper lands for water shortage, he talks about the fair share of scare resources and rights protection for upstream farmers. Keywords. Natural resource management, Forest preservation, Farmer livelihoods. JEL. A10.